PENGARUH TEACHING GAMES FOR UNDERSTANDING TERHADAP PENINGKATAN KETERAMPILAN BERMAIN SEPAKBOLA : Penelitian Eksperimen Terhadap Siswa Kelas V di SDN 05 Kumbara Utama - Rohim, Alqindo Algozali (2017)
The purpose of this research is to know the influence of teaching model application which is Teaching Games for Understanding to increase the skill in soccer plays. The method that used in this research is experiment method. While the design that used in this research is Pretest Posttest Control Group Design. The instrument in this research is using the Game Performance Assessment Instrument (GPAI) test. The population of this research is the all of students of SDN 05 Kumbara Utama. The sample used in this research is 34 students taken from 5th grade and the sample determinant in this research is the simple random sampling technique. Based on the result of the research, the influence of teaching approach application which is Teaching Games for Understanding and technique approach have show the increase of skill in soccer plays. However based on the data calculation result the uses of Teaching Games of Understanding gives better than Technique approach impact to the increase of skill in soccer plays.;---Tujuan penelitian ini adalah untuk mengetahui pengaruh penggunaan Teaching Games for Understanding terhadap peningkatan keterampilan bermain sepakbola. Metode yang digunakan dalam penelitian ini adalah metode eksperimen. Desain penelitian menggunakan Pre-test Post-test Control Group Design. Instrumen dalam penelitian ini menggunakan teknik Game Performance Assessment Instrument (GPAI). Populasi dalam penelitian ini adalah seluruh siswa di SD Negeri 05 Kumbara Utama, sedangkan sampel dalam penelitian ini berjumlah 34 orang. Penentuan sampel menggunakan teknik Simple Random Sampling. Berdasarkan analisis dan pengolahan data, baik Teaching Games for Understanding maupun Pendekatan Teknik, keduanya memberikan pengaruh terhadap keterampilan bermain, pengaruh Teaching Games for Understanding lebih baik dibandingkan Pendekatan Teknik terhadap peningkatan keterampilan bermain sepakbola.